Cost‐effectiveness analysis of tension‐free vaginal tape vs burch colposuspension for female stress urinary incontinence in the USA. (14th June 2013) - Laudano, Melissa A.; Seklehner, Stephan; Chughtai, Bilal; Lee, Una; Tyagi, Renuka; Kavaler, Elizabeth; Te, Alexis E.; Kaplan, Steven A.; Lee, Richard K.
<x xml:space="preserve">Abstract</x> Objective To compare the cost‐effectiveness (CE) of tension‐free vaginal tape (TVT) with that of burch colposuspension (BC) for the treatment of female stress urinary incontinence (SUI). Materials and Methods A Markov‐chain decision model was created to simulate treatment of SUI with TVT or BC using Treeage Pro 2011 software (Treeage Software Inc., Williamstown, MA, USA). Costing data were obtained from the Medicare Resource‐Based Relative Value Scale. Data regarding the success of TVT vs BC were obtained from the peer‐reviewed literature, as were corresponding utilities for different continence states. The CE of each procedure was calculated and compared, and sensitivity analyses were performed. Results At 10‐year follow‐up, TVT was more cost‐effective (CE = 1495/quality‐adjusted life year [QALY]) than BC (CE = 1824/QALY). Sensitivity analysis showed that TVT was more cost‐effective than BC if the cost of the TVT device was <3220. If the probability of success after TVT was <42%, then BC became the more cost‐effective strategy (CE = 1827/QALY). Conclusion Our study showed that TVT was more cost‐effective than BC as a treatment for female SUI. Both cost of TVT device and efficacy of the procedure affect the CE analysis.